Amar Putusan Pada Kewenangan Judicial Review di Mahkamah Konstitusi - Dedeng Dedeng (Universitas Sriwijaya, 2018)
The Constitutional Court as an Indonesian state institution in the judicial review of the law against the 1945 Constitution of the Republic of Indonesia has been regulated by Law Number 24 Year 2003. Testing the Act against the Constitution of the State of the Republic of Indonesia Year 1945 to produce an amar decision of the Constitutional Court in practice should still refer to the provisions of the Constitutional Court Law is Article 56 of the Constitutional Court Law. The research method used is prescriptive legal research, with the approach of legislation, case approach and historical approach. The types and sources of legal materials include primary and secondary legal materials. The technique of drawing conclusions using deductive thinking logic is the way of thinking of general statements drawn conclusions that are specific to obtain answers to the problems to be discussed in this journal thesis.Based on the result of the research, the decision of the Constitutional Court namely the ruling declared the request is unacceptable, the verdict states the petition is granted, the verdict says the petition is granted, and the verdict declares that the verdict is rejected. The result of the research about the ruling in practice in the process of examining the law against the 1945 Constitution of the State of the Republic of Indonesia in the Constitutional Court is based on the results of the study of the 2016, 2017 and 2018 decisions are varying rulings namely the decision of the Constitutional Court which states to grant partial, denied part of it, declared void, declared unauthorized, declared the interlocutory / provisional, declared withdrawn, refused entirely, granted whole and unacceptable. The decision of the Constitutional Court should be the ruling that has been regulated in accordance with Article 56 of Law Number 24 Year 2003 regarding the Constitutional Court. Institutions of the Constitutional Court on the verdict should still refer to the provisions of the ruling as stipulated and regulated in the Law of the Constitutional Court itself. The House of Representatives (DPR) body needs to supplement the provisions of Article 56 of Law Number 24 Year 2003 regarding the Constitutional Court as amended into Law Number 8 Year 2011 regarding the amendment of Law Number 24 Year 2003 The government or the President needs to support the fulfillment of the legal basis to accommodate the varied decisions of the Constitutional Court.